Exploring the Potential for Renewable Energy Consumption in Reducing Environmental Degradation in Somalia - Nor, Bile Abdisalan; Yusof, Yusniliyana; Warsame, Zakarie Abdi (International Journal of Energy Economics and Policy, 2024)
Somalia has a relatively small amount of forested land, covering only about 10.5% of the nation’s total land area. The reason for this is that much of the country’s tropical forests, which were originally located along the Shabelle and Jubba rivers reclaimed agricultural land. This study examines the relationship between environmental degradation and various variables, including renewable energy consumption, GDP, FDI inflow, and population. The study employed ARDL model to analyze the econometric relationship between various latent variables. This study found that that in Somalia, renewable energy consumption, GDP and FDI have both short-term and long-term negative and statistically significant effects on environmental degradation. However, FDI exhibits a positive and significant relationship with environmental degradation in both the short and long run. The findings of the study suggest that there is a positive correlation between renewable energy consumption and economic growth, and a negative correlation between renewable energy consumption and environmental degradation. The study also suggests that FDI may play a role in promoting renewable energy consumption and economic growth. The limitation of this study is that the study does not control for all of the potential factors that could influence the relationship between the variables. For example, the study does not control for the level of corruption in Somalia, which could potentially affect both economic growth and environmental degradation. Future research should address the limitations of this study by controlling for all of the potential factors that could influence the relationship between the variables.